Improving the supercapacitor performance of activated carbon materials derived from pretreated rice husk. (15th December 2021) - Chen, Jialian; Liu, Jinling; Wu, Dandan; Bai, Xin; Lin, Yuting; Wu, Tingting; Zhang, Chi; Chen, Denglong; Li, Hongzhou
Highlights: Providing a better pretreatment scheme of rice husk carbon. Specific surface area is high and well-developed pore structure. Silica selectively leaching-out can adjust pore structure. Pretreated activated carbon electrode has superior cycling stability and high specific capacity. Abstract: In this study, the application of high specific surface area activated carbon prepared from rice husk (RHAC) as a supercapacitor electrode was reported. To enhance the pore-making efficiency of activator, pretreatment using NaOH solution or K2 CO3 solution was adopted. Seven samples of RHAC were prepared at different pretreatment conditions and characterized with their specific surface area, pore structure and electrochemical performance. The alkaline solution pretreatment of rice husk developed a more advanced mesopore system, which greatly increased the RHAC specific surface area and electrochemical performance when applied to the supercapacitor electrode. The maximum specific capacitance (up to 325 F g −1 ) and outstanding cycling stability (up to 285 F g −1 after 10, 000 cycles) were obtained by the RHAC-b sample (specific surface area of 2556.8 m 2 g −1 ) which was prepared with 10% K2 CO3 pretreatment.